2018
DOI: 10.30813/jab.v10i1.988
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Penerapan Manajemen Risiko Terhadap Kinerja Keuangan Industri Perbankan

Abstract: <p><em><span style="font-family: Times New Roman; font-size: medium;">The role of the large banking industry in the Indonesian economy affects banking governance, where prudence is strongly emphasized. Such caution is a reflection of the attitude of responsibility towards the trust given by the community. To address the risks involved in banking operations, risk management is a much-needed solution, which is used to identify, measure, monitor, and control risks arising from bank operations. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 3 publications
1
7
0
9
Order By: Relevance
“…The findings in this study regarding the effect of CAR on profitability (ROA) are consistent with the findings made by Efriyenty (2020); Khalifaturofi'ah (2021); Pratiwi, and Kurniawan (2018). This study found that solvency risk proxied by the Capital Adequacy Ratio (CAR) has a positive and significant effect on financial performance as proxied using Return on Equity (ROE).…”
Section: The Influence Of Solvency Risk On Profitabilitysupporting
confidence: 91%
See 1 more Smart Citation
“…The findings in this study regarding the effect of CAR on profitability (ROA) are consistent with the findings made by Efriyenty (2020); Khalifaturofi'ah (2021); Pratiwi, and Kurniawan (2018). This study found that solvency risk proxied by the Capital Adequacy Ratio (CAR) has a positive and significant effect on financial performance as proxied using Return on Equity (ROE).…”
Section: The Influence Of Solvency Risk On Profitabilitysupporting
confidence: 91%
“…Other research by Efriyenty (2020); Khalifaturofi'ah (2021); Pratiwi and Kurniawan (2018) found that solvency risk proxied by the Capital Adequacy Ratio (CAR) has a positive and significant effect on financial performance as proxied using Return on Assets (ROA). However, these findings contradict the findings of Sriyana (2015), who found that solvency risk proxied by the Capital Adequacy Ratio (CAR) had a negative and significant effect on financial performance as proxied using Return on Assets (ROA).…”
Section: The Relationship Between Solvency Risk and Profitability Of ...mentioning
confidence: 99%
“…Beberapa aplikasi manajemen risiko yang digunakan untuk mendukung pelaksanaan proses manajemen risiko yang tepat waktu dan akurat antara lain sistem manajemen risiko kredit (CRMS), sistem pemeringkatan internal, sistem penilaian, perangkat risiko operasional (PERISKOP) dan aplikasi manajemen risiko pasar. Untuk terus beradaptasi dengan era digital yang semakin meningkat, BNI telah menyiapkan solusi manajemen risiko yang selaras dengan rencana strategis TI, antara lain: Menurut (Pratiwi & Kurniawan, 2018) bank yang berperan sangat penting dalam sistem keuangan mengusulkan beberapa peran penting bank, yaitu transfer aset, transaksi, likuiditas, efisiensi. Oleh karena itu, dalam hal ini, pemerintah juga telah mengambil beberapa langkah strategis untuk menghadapi era perdagangan bebas, dengan memutuskan untuk menggabungkan beberapa bank milik negara seperti Bank Bumi Daya, Bank Dagang Negara, Bank Ekspor dan Bank Pembangunan Indonesia ke dalam Bank Mandiri, Serta Bank Rakyat Indonesia dan Bank Tabungan Negara dan Bank Negara Indonesia 1946 masih beroperasi sampai sekarang.…”
Section: Pembahasan Manajemen Risiko DI Bniunclassified
“…If it is related to the issue of Risk Management, Internal Control, and Corporate Governance, then agency theory is more relevaTor to overcominge agency problems, it is deemed necessary to create a control design strategy to ensure the achievement of organizational goals that provides maximum results for agents and principals. This strategy uses tools designed in the form of Risk Management processes, Internal Control, Corporate Governance, and, the establishment of the Internal Audit function, taking into account costs and benefits (Pratiwi & Kurniawan, 2018).…”
Section: Literature Review Agency Theorymentioning
confidence: 99%